ANALISIS SOSIO-HISTORIS TEKS KEJADIAN 1:28 DAN IMPLIKASINYA BAGI KELAHIRAN ANAK DALAM PERNIKAHAN KRISTEN - Purim Marbun; Hasudungan Sidabutar (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
Marriage is a conscious choice and becomes one of the essential things in the journey of human life. Therefore, every couple who decides to start a household life brings their own needs, desires and aspirations, including the desire to have children. But the problem is there are married couples who are not blessed with children. If this is related to Christian marriage, how does the Christian faith respond to it? This paper explores the command to be fruitful and multiply in Genesis 1: 28. The method used is hermeneutic with a socio-historical approach to look at the text's origins so that the text's application is in accordance with the context. The results of the study show that the background of Genesis 1: 28 cannot be separated from the events of the life of the Jewish nation (Israel) when they had just returned from exile supported by the Persian empire. As leaders, the priests of Zadok needed many descendants to retrieve inherited land, manage land to revive the economy and pay taxes for the benefit of the lives of the Zadok priests and servants in the temple cult. Based on this, the purpose of Christian marriage is not for that, so physical offspring in Christian marriage is not absolute. The physical birth of offspring in a Christian marriage is a divine mystery. Therefore, a Christian couple with no heart need not feel guilty, let alone think they did not fulfil the commandment in Genesis 1: 28.